`It`s not mind blowing really….it`s about keeping people happy`: the perceptions of player welfare managers in Rugby Super League - Lewis, K.; Rodriguez, A.; Kola-Palmer, S.; Sherretts, N. (Qualitative Research in Sport, Exercise and Health, 2018)
At a time when the welfare needs of individuals within powerful organisations, such as professional sport, are being scrutinised it is appropriate to look at what is being done to support athletes and what more may be needed. The RFL, in recognition of the need for welfare support, introduced player welfare managers to all Super League clubs in 2011. Using an interpretivist approach, we report the findings from a series of semi-structured interviews with player welfare managers (PWMs) that explored the PWMs` perceptions of player welfare, what impact they believe they are having on player welfare, and what else is needed to enhance the service. The PWMs perceive that they have been an important resource for players, independent of the club and coaches, which has allowed players to seek support for a range of issues. The use of the services provided by PWMs increased over the time between interviews, this, it is thought, is due in part to a change of culture within the sport. The PWMs felt the head coach, along with the backing of the club, and the RFL structure were important in the services being accessible and accepted. The PWMs were struggling to meet the demands of their job roles, which were largely part time. However, since the results of this and other studies were made accessible to the RFL, large-scale changes to welfare provision have been made, including making the PWMs` posts full-time. This is seen as an important contribution and commitment to players` welfare needs.